Harmoni dalam budaya Jawa - Roqib, Moh. (Pustaka pelajar, 2007)
On harmonious life from Javanese culture perspective
Includes bibliographical references (p. 245-254)
Keywords: Javanese (Indonesian people); Ethics; Javanese